(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
In my classroom, I see a black child. I hear her soft voice: “Mwalimu unaniona?Mwalimu unajua mimi nani? Mwalimu nakupenda.”2 I see her mother wearing her kitenge and kitambaa gliding gracefully toward me. I do not know where to start – their oddity is palpable. This child and her family could very well be from Mars. And I continue to wonder: If I were to reprimand her, would she cry? If I were to praise her, would she smile? Does she have any friends? Does she even need them? Is she afraid of the same things that I fear? What if not? Can I still care about this child whom I do not even understand? This child’s expression of humanity is so hard to comprehend that she becomes invisible, hidden behind her oddity as if behind a mask.